Transcription Factor ZNF281: A Novel Player in Intestinal Inflammation and Fibrosis - Pierdomenico, Maria; Palone, Franscesca; Cesi, Vincenzo; Vitali, Roberta; Mancuso, Anna Barbara; Cucchiara, Salvatore; Oliva, Salvatore; Aloi, Marina; Stronati, Laura (Frontiers in Immunology, 2018)
Background and aims: recent evidences reveal the occurrence of a close relationship among epithelial to mesenchymal transition (EMT), chronic inflammation and fibrosis. ZNF281 is an EMT-inducing transcription factor (EMT-TF) involved in the regulation of pluripotency, stemness and cancer. The aim of this study was to investigate in vitro, in vivo and ex vivo a possible role of ZNF281 in the onset and progression of intestinal inflammation. A conceivable contribution of the protein to the development of intestinal fibrosis was also explored. Methods: human colorectal adenocarcinoma cell line, HT29, and C57BL/6 mice were used for in vitro and in vivo studies. Mucosal biopsy specimens were taken during endoscopy from 29 pediatric patients with Crohn’s disease (CD), 24 with ulcerative colitis (UC) and 16 controls. ZNF281 was knocked down by transfecting HT29 cells with 20nM small interference RNA (siRNA) targeting ZNF281 (siZNF281). Results: we show for the first time that ZNF281 is induced upon treatment with inflammatory agents in HT29 cells, in cultured uninflamed colonic samples from CD patients and in DSS-treated mice. ZNF281 expression correlates with the disease severity degree of CD and UC patients. Silencing of ZNF281 strongly reduces both inflammatory (IL-8, IL-1β, IL-17, IL-23) and EMT/fibrotic (SNAIL, Slug, TIMP-1, vimentin, fibronectin and α-SMA) gene expression; besides, it abolishes the increase of extracellular-collagen level as well as the morphological modifications induced by inflammation. Conclusions: the identification of transcription factor ZNF281 as a novel player of intestinal inflammation and fibrosis allows a deeper comprehension of the pathogenetic mechanisms underlying inflammatory bowel disease (IBD) and provide a new target for their cure.